The public barrio high schools in Bulacan - Ventura, Felicitas San Juan 1934- ([Quezon City [publisher not identified], 1971)
This study determined the status of the public barrio high schools in the Division of Bulacan. There were sufficient evidences to show that the requirements of the Bureau of Public Schools regarding enrolment, organization, sources of funds, qualifications of teachers and staffing, and instructional facilities were satisfactorily met by the twenty barrio high schools established in Bulacan from July 1967 to July 1970.
Thesis (Master in Education)--University of the Philippines.
Keywords: Rural schools -- Philippines -- Bulacan (Province).